2012
DOI: 10.1039/c2lc40530j
|View full text |Cite
|
Sign up to set email alerts
|

A novel deep reactive ion etched (DRIE) glass micro-model for two-phase flow experiments

Abstract: In the last few decades, micro-models have become popular experimental tools for two-phase flow studies. In this work, the design and fabrication of an innovative, elongated, glass-etched micromodel with dimensions of 5 6 35 mm 2 and constant depth of 43 microns is described. This is the first time that a micro-model with such depth and dimensions has been etched in glass by using a dry etching technique. The micro-model was visualized by a novel setup that allowed us to monitor and record the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…The micromodel used in this work was the same micromodel used in the work of Karadimitriou et al . []. It was an elongated PDMS micromodel, with overall dimensions of the pore network being 5 × 30 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The micromodel used in this work was the same micromodel used in the work of Karadimitriou et al . []. It was an elongated PDMS micromodel, with overall dimensions of the pore network being 5 × 30 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Middle East is dominated by carbonate rocks, with around 70% of oil and 90% of gas reserves held within these reservoirs. [23][24][25] Various fabrication techniques have been employed to build micromodels, 8,9 including plasma etching of silicon, 26 deep reactive ion etching of glass, 27,28 and soft lithography with polymeric materials. 21 Treiber et al investigated 50 samples and showed that only 8% of the carbonate reservoir rocks were water-wet, 8% intermediate-wet, and 84% oil-wet.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup is the one used in various studies by Karadimitriou et al (2012Karadimitriou et al ( , 2013. The micro-model used for the experiment had a rectangular shape with dimensions 2.5×1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Both quasi-static and dynamic drainage experiments were performed in a poly-dimethylsiloxane (PDMS) micro-model (Karadimitriou et al 2012). The fluids used as the wetting and the non-wetting phase were Fluorinert FC-43 and water dyed with ink, respectively.…”
Section: Introductionmentioning
confidence: 99%